Inactivation of the FLCN Tumor Suppressor Gene Induces TFE3 Transcriptional Activity by Increasing Its Nuclear Localization - Hong, Seung-Beom (Public Library of Science, 2010)
BACKGROUND: Germline mutations in a tumor suppressor gene FLCN lead to development of fibrofolliculomas, lung cysts and renal cell carcinoma (RCC) in Birt-Hogg-Dubé syndrome. TFE3 is a member of the MiTF/TFE transcription factor family and Xp11.2 translocations found in sporadic RCC involving TFE3 result in gene fusions and overexpression of chimeric fusion proteins that retain the C-terminal DNA binding domain of TFE3. We found that GPNMB expression, which is regulated by MiTF, was greatly elevated in renal cancer cells harboring either TFE3 translocations or FLCN inactivation. Since TFE3 is implicated in RCC, we hypothesized that elevated GPNMB expression was due to increased TFE3 activity resulting from the inactivation of FLCN. METHODOLOGY/PRINCIPAL FINDINGS: TFE3 knockdown reduced GPNMB expression in renal cancer cells harboring either TFE3 translocations or FLCN inactivation. Moreover, FLCN knockdown induced GPNMB expression in FLCN-restored renal cancer cells. Conversely, wildtype FLCN suppressed GPNMB expression in FLCN-null cells. FLCN inactivation was correlated with increased TFE3 transcriptional activity accompanied by its nuclear localization as revealed by elevated GPNMB mRNA and protein expression, and predominantly nuclear immunostaining of TFE3 in renal cancer cells, mouse embryo fibroblast cells, mouse kidneys and mouse and human renal tumors. Nuclear localization of TFE3 was associated with TFE3 post-translational modifications including decreased phosphorylation. CONCLUSIONS/SIGNIFICANCE: Increased TFE3 activity is a downstream event induced by FLCN inactivation and is likely to be important for renal tumor development. This study provides an important novel mechanism for induction of TFE3 activity in addition to TFE3 overexpression resulting from Xp11.2 translocations, suggesting that TFE3 may be more broadly involved in tumorigenesis.